Mechanical property and meso-structure assessment of Ti6Al4V parts as a function of high-speed selective laser melting practice (Additive Manufacturing) - Nyakunu, Chenesai (Department of Mechanical Engineering, 2023)
The use of titanium and titanium alloys, particularly titanium-6-aluminium-4-vanadium (Ti6Al4V), manufactured by 3D printing, also known as additive manufacturing, is fast evolving in several industries including the aerospace industry, medical industry, and the automotive industry. At present, titanium parts fabricated by additive manufacturing techniques such as the selective laser melting practice are built at conventional laser scan speeds typically between 0.1 m/s and 1 m/s. This project is focused on investigating the influence of high laser scan speeds on the microstructure and mechanical properties of Ti6Al4V fabricated by the selective laser melting technique. Building material at much higher scan speeds allows for a higher rate of productivity and efficiency as more parts can be built in a shorter space of time. The aim of this project is to ensure that the integrity and mechanical behaviour of the Ti6Al4V parts at the high scan speeds is still maintained by investigating whether acceptable mechanical properties are still achieved when material is built at higher scan speeds. The material tested in this project was built by the selective laser melting (SLM) technique at four different high scan speeds namely 5.75 m/s, 6.0 m/s, 6.25 m/s and 6.5 m/s. The material for mechanical testing consisted of tensile specimens and compact-tension (CT) specimens for fracture toughness (FT) testing and fatigue crack growth rate (FCGR) testing respectively. The same material was used for microstructure analysis. Furthermore, the tensile specimens were fabricated in different build orientations namely X-TA, Y-TA, and Z-TA to investigate the effect of build orientation on tensile properties. During the SLM process, considerable thermal related stresses develop in the material being built. After fabrication, a heat treatment protocol was therefore applied to the material for stress relief. The material was heated at 600°C for two hours then cooled in air. Tensile testing was performed on the SLM Ti6Al4V built tensile bars according to the ASTM E8/E8M standard on the Zwick machine at a strain rate of 10-3 /s in conjunction with a video extensometer for more accurate results. Specimens were loaded in tension with force of approximately 20 000N. The results indicated that there is no significant influence of high scan speed on the tensile properties of the material tested as there was no difference observed in tensile properties of the material built at the four different high scan speeds. The same phenomenon was observed with build orientation. The tensile properties of the specimens built in the horizontal direction (X-TA and Y-TA) and the specimens built in the vertical direction (Z-TA) were within the same range. The FCGR and FT tests were performed on the ESH servo hydraulic fatigue machine at room temperature according to the ASTM E647-15 and E399 standards, respectively. The FCGR tests were conducted at a load range of 1.3kN and stress ratio of 0.1. The results indicated that there is no difference in FCGR behaviour with respect to scan speed between the 5.75 m/s and 6.0 m/s specimens as one set and no difference between the 6.25 m/s and 6.5 m/s specimens as the other set, but a difference is observed between the two sets of speeds. All specimens however, displayed reasonable resistance to crack growth. The FT tests were performed at a crosshead speed of 1 mm/min. The results indicated that high scan speed has no significant influence on the fracture toughness of SLM Ti6Al4V material as there was no difference observed in fracture toughness of the materials with increase in scan speed. The techniques used for microstructure analysis were light microscopy and scanning electron microscopy (SEM). Light microscopy was performed to reveal the microstructure and surface topography of the material built at the four different high scan speeds and three different build orientations. The results indicated that high scan speed has no significant influence on the microstructure of the material investigated. The results also indicated that build orientation influences the microstructure of the material tested. A difference in microstructure, particularly the orientation of β-grains, was observed with build orientation. The X-TA and Y-TA specimens have β-grains aligned more perpendicular to the tensile axis whilst the Z-TA specimens have the β-grains aligned more parallel to the tensile axis. However, this difference in β-grain orientation did not influence the tensile properties of these specimens to a greater extent. SEM was performed to obtain quantitative information on microstructure, particularly porosity, and for β-grain reconstruction by electron backscatter diffraction (EBSD) for the material at a much higher magnification and depth of field. The results indicated that high scan speed has no influence on porosity of the material tested as no difference was observed in the number and size of pores amongst the samples built at the four high scan speeds. However, average relative density of 97-99% was reported for these specimens which is lower in comparison with average relative density of >99% reported for the majority of the specimens built at conventional scan speeds. EBSD analysis shows that there is no difference in the size and morphology of reconstructed β-grains across the material built at the high scan speed. It is concluded that there is no significant influence of high scan speed on the microstructure and mechanical properties of SLM Ti6Al4V within the scan speed range of 5.75 m/s to 6.5 m/s investigated in this project. The specimens built at the specified scan speeds have similar energy density input which attributes to the similar microstructure and mechanical behaviour of the specimens observed.